GAMIFICATION IN LANGUAGE ASSESSMENT: ENHANCING MOTIVATION AND PERFORMANCE - Abdushukurova Oysha Sirojiddin qizi; Khonsaidova Maktuba Makhamadalievna (TADQIQOTLAR, 2026)
ABSTRACT This study explores the role of gamification in enhancing motivation and improving performance in language assessment settings. It examines how game-based elements influence learners’ attitudes, participation levels, and achievement outcomes. Drawing on contemporary educational theories and empirical research, the paper highlights the psychological mechanisms underlying gamified learning environments, including increased engagement, immediate feedback, and goal-oriented progression.